2014
DOI: 10.4103/0259-1162.143151
|View full text |Cite
|
Sign up to set email alerts
|

The recovery time of sevoflurane and desflurane and the effects of anesthesia on mental and psychomotor functions and pain

Abstract: Background:Inhalation anesthetics have many advantages for outpatient general anesthesia, such as minimal postoperative side-effects and rapid and full recovery. The aim of this randomized study was to compare the postoperative recovery time of sevoflurane and desflurane and to observe the effects of anesthesia on mental, psychomotor and cognitive functions and pain in outpatients undergoing arthroscopic surgery.Patients and Methods:This study included 40 American Society of Anesthesiologists I-II patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 12 publications
3
29
0
Order By: Relevance
“…However, there was no difference in the incidence of pain between the two volatiles, which is in accordance with previous studies assessing pain prior to discharge. [6, 7, 23] Similarly, we found no differences in cognitive Recovery between sevoflurane and desflurane, which is also consistent with studies showing no differences in the immediate postoperative period. [7, 8, 2325] Nevertheless, the current study went further to describe potential differences in intermediate and long-term recovery.…”
Section: Discussionsupporting
confidence: 91%
“…However, there was no difference in the incidence of pain between the two volatiles, which is in accordance with previous studies assessing pain prior to discharge. [6, 7, 23] Similarly, we found no differences in cognitive Recovery between sevoflurane and desflurane, which is also consistent with studies showing no differences in the immediate postoperative period. [7, 8, 2325] Nevertheless, the current study went further to describe potential differences in intermediate and long-term recovery.…”
Section: Discussionsupporting
confidence: 91%
“…Although early studies have reported high incidences of postoperative hypoxemia (as high as 55%) [ 28 ], incidences have decreased to around 20% by the mid-2010s [ 25 27 , 29 ]. Such a decrease might have been related to the increased availability of new and short-acting anesthetic drugs [ 30 , 31 ], comprehensive pharmacological knowledge, and multimodal analgesia techniques for maximizing postoperative pain relief while minimizing side effects, and new minimally invasive surgery options. Thus, routine supplemental oxygen administration to prevent hypoxemia might not be necessary in most postoperative patients in recent years.…”
Section: Prevention Of Postoperative Hypoxemiamentioning
confidence: 99%
“…Currently, sevoflurane is widely used in clinical because of its rapid onset of action, quick and complete recovery, good controllability and fewer side effects [19]. But due to its unclear pharmacological mechanism, the effects of sevoflurane on vital organs such as lung, kidney, liver and brain are also inconsistent even through there are many related reports In this study, we found that 2% sevoflurane inhibited HUVECs migration function time-dependently.…”
Section: Discussionmentioning
confidence: 59%